[tex]-4(10n-6)=-406[/tex]
1. You remove the parenthesis, the term outside the parenthesis affect each term in the parenthesis (you multiply -4 for each term in the parenthesis):
[tex]\begin{gathered} -4(10n)-4(-6)=-406 \\ -40n+24=-406 \end{gathered}[/tex]
The mistake was in the step 1 as the -4 was not multiplied for both terms in the parenthesis.
2. Substract 24 in both sides of the equation:
[tex]\begin{gathered} -40n+24-24=-406-24 \\ -40n=-430 \end{gathered}[/tex]
3. Divide into -40 both sides of the equation:
[tex]\begin{gathered} \frac{-40n}{-40}=\frac{-430}{-40} \\ \\ n=\frac{430}{40} \end{gathered}[/tex]
4. Simplify:
[tex]n=\frac{430}{40}=\frac{43}{4}=10.75[/tex]Then, the answer is n=10.75